2015
DOI: 10.4103/1817-1745.165716
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of acute flaccid paralysis: Human coronaviruses

Abstract: Acute flaccid paralysis (AFP) is a life-threatening clinical entity characterized by weakness in the whole body muscles often accompanied by respiratory and bulbar paralysis. The most common cause is Gullian–Barre syndrome, but infections, spinal cord diseases, neuromuscular diseases such as myasthenia gravis, drugs and toxins, periodic hypokalemic paralysis, electrolyte disturbances, and botulism should be considered as in the differential diagnosis. Human coronaviruses (HCoVs) cause common cold, upper and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 8 publications
1
57
0
7
Order By: Relevance
“…Reports describing the epidemiology of respiratory viruses other than influenza among ED patients [17] and clinical concerns over viruses other than influenza [18] continue to evolve and lend support for comprehensive panel-based approaches to respiratory virus testing. Whether syndromic-respiratory virus testing can be performed during ED visits in time to influence management is currently a debate, and many panel-based respiratory tests are often reserved or hospitalized or acutely ill patients because the utility of comprehensive respiratory virus testing has not been established among ED populations.…”
Section: Discussionmentioning
confidence: 99%
“…Reports describing the epidemiology of respiratory viruses other than influenza among ED patients [17] and clinical concerns over viruses other than influenza [18] continue to evolve and lend support for comprehensive panel-based approaches to respiratory virus testing. Whether syndromic-respiratory virus testing can be performed during ED visits in time to influence management is currently a debate, and many panel-based respiratory tests are often reserved or hospitalized or acutely ill patients because the utility of comprehensive respiratory virus testing has not been established among ED populations.…”
Section: Discussionmentioning
confidence: 99%
“…As other viruses listed herein, HCoV are neurotropic and potentially neurovirulent. Even though no clear cause and effect link has ever been made with the onset of human neurological diseases, their neuropathogenicity is being increasingly recognized in humans, as several recent reports associated cases of encephalitis [244], acute flaccid paralysis [271] and other neurological symptoms, including possible complications of HCoV infection such as Guillain-Barré syndrome or ADEM [249,[272][273][274][275][276][277][278][279]. The presence and persistence of HCoV in human brains was proposed to cause long-term sequelae related to the development or aggravation of chronic neurological diseases [245][246][247][248][280][281][282].…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 99%
“…This suggest that better surveillance, diagnoses and deepened virus-host interactions studies are warranted in order to gather more knowledge that will make possible the development of therapeutic strategies to prevent or treat occurrences. Potential Short-Term Neuropathologies SARS-CoV, HCoV-OC43 and -229E are naturally neuroinvasive and neurotropic in humans and therefore potentially neurovirulent [220,244,245,249,270,271]. Furthermore, animal models showed that SARS-CoV could invade the CNS primarily through the olfactory route [265] or even after an intra-peritoneal infection [284], and induce neuronal cell death [265,284].…”
Section: Human Coronaviruses In the Cns: Possible Associated Neurologmentioning
confidence: 99%
“…To circumvent these limitations, we developed a model of HCoV neuropathogenesis by taking advantage of the natural susceptibility of mice to neuroinvasion by the widely circulating HCoV OC43 human strain. Upon infection, mice indeed developed neurological symptoms reminiscent of the afflictions reported in several human patients (10,13,(19)(20)(21), such as encephalitis, transient flaccid paralysis, and long-term persistence in surviving mice (23,24,(30)(31)(32)(33). Knowledge of the paths and underlying mechanisms governing the propagation of the virus from the upper respiratory tract to and within the CNS is currently incomplete, which hinders the elaboration of antiviral countermeasures adapted to this particular host compartment.In our study, we defined the path taken by HCoV OC43 (34, 35) to access and spread to and within the CNS and studied the underlying modes of intercellular propagation to better understand its neuropathogenesis in both humans and mice.…”
mentioning
confidence: 99%
“…In the second, intranasal inoculation was used to achieve more realistic levels expected upon more natural delivery. To facilitate the contact of the virus with subepithelial nerves, the epithelial barrier was bypassed in the third group by injecting the inoculum 13 8/12 66 15 8/12 66 17 2/12 17 19 1/12 8…”
mentioning
confidence: 99%